Usefulness of neutrophil‐to‐lymphocyte ratio in predicting progression and survival outcomes after atezolizumab–bevacizumab treatment for hepatocellular carcinoma. Issue 1 (4th October 2022) - Ochi, Hironori; Kurosaki, Masayuki; Joko, Kouji; Mashiba, Toshie; Tamaki, Nobuharu; Tsuchiya, Kaoru; Marusawa, Hiroyuki; Tada, Toshifumi; Nakamura, Shinichiro; Narita, Ryoichi; Uchida, Yasushi; Akahane, Takehiro; et al.
Abstract: Aim: We investigated pretreatment neutrophil‐to‐lymphocyte ratio (NLR) for predicting survival outcomes of atezolizumab plus bevacizumab therapy for hepatocellular carcinoma (HCC) and determined the predictive ability of combined liver reserve–NLR. Methods: This retrospective, multicenter study enrolled 242 patients receiving atezolizumab plus bevacizumab for unresectable HCC. Pretreatment NLR <2.56 was designated as the "low group" and NLR ≥2.56 as the "high group" (120 and 122 patients, respectively). Propensity score‐matched analysis was undertaken between the low and high groups. Results: In this cohort, the objective response and disease control rates were 20% and 72.5%, respectively, in the low group and 19.6% and 72.9%, respectively, in the high group. After matching, median progression‐free survival (PFS) time was 283 and 167 days in the low and high groups, respectively ( p  = 0.022). Neutrophil‐to‐lymphocyte ratio ≥2.56 (hazard ratio [HR], 1.54; 95% confidence interval [CI], 1.05–2.28; p  = 0.028), modified albumin–bilirubin index (mALBI) grade 2b or 3 (HR 1.55; 95% CI, 1.05–2.29; p  = 0.025), and protein induced by vitamin K absence or antagonist‐II ≥ 400 (HR 2.03; 95% CI, 1.36–3.02; p  = 0.001) were significantly associated with PFS in univariate analysis using the Cox proportional hazards model. In cases involving mALBI grade 1 or 2a ( n  = 131), the median PFS time was not reached in the low group, whereas it was 210 days in the high group ( p  = 0.037). Conclusions: Pretreatment NLR is a simple tool for routine measurement in clinical practice. It can predict PFS in patients with unresectable HCC treated with atezolizumab plus bevacizumab, especially mALBI grade 1 or 2a.